PENDUGAAN BIOMASSA KARBON SERASAH DAN TANAH PADA HUTAN TANAMAN (Shorea leprosula Miq) SISTEM TPTII PT. SUKA JAYA MAKMUR - tah, Rosi; Herawatiningsih, Ratna; Hardiansyah, Gusti (Universitas Tanjungpura, 2013)
Global warming is one of the important environmental issues that currently concern to various parties. Related to the phenomenon, environmentalists begin to worry what conditions of earth will be if global warming continues. Forests has important roles through three ways;the first is as a carbon pool, the second is as a source of CO2 and the third is as carbon sink. If the forest is properly managed, it will be able to overcome the excessive amount of carbon in the atmosphere by storing carbon in the form of biomass which is either above or below the ground surface. One forest stands whose carbon can be assessed is the forest plantation of red meranti (Shorea leprosula Miq). This study aimed to estimate the amount of biomass carbon of litter and soil organic carbon in the forest plantation of red meranti (Shorea leprosula Miq). This study used proposive system with composite of litter and soil sampling in the field by making a diagonal plot size is 100 100 meters, then make a plot of 1 1 meter as a plot for litter and soil sampling which is the depth of 20 cm below the stands of red Meranti plantation. Based on the results of the research, total biomass ranged between 31.72 and 61.14 ton / ha. The better an ecosystem of an in area is, the more fertilezed that area will be and, indirectly the higher the litter carbon will be produced.. Based on the results of litter carbon conten which ranged from 11 to 23.5%. a year growing plant gained 11%, while a 7 year growing plant gained 23.5%. The longer the age of the is, the greater carbon will be produced. Based on the studys finding, the level of soil organic is low ranged from 1.08 to 1.96%. The level of soil organic carbon shows that the longer the age of the plant is, the greater the level of content of soil organic carbon. Keywords: Biomass ,Carbon, litter, soil organic carbon, Shorea leprosula Miq.